2014
DOI: 10.29309/tpmj/2014.21.06.2247
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cardiotocography;

Abstract: Objective: To observe the effect of abnormal Cardiotocography to delivery interval on perinatal outcome in terms of Apgar score. Study design: Descriptive case series study. Place and duration of study: Baqai Medical University department of obstetrics and gynecology Fatima Hospital Karachi from Jan 2011 to July 2011. Material and method: One hundred patients were registered who had pathological Cardiotocography. Bishop’s score was noted and decision to deliver the patient was made according to the abnormality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The admission CTG had a high sensitivity of 91.0% in predicting base deficit of >−12 mmol/L, a specificity of 68.8%, a positive predictive value of 96.6%, a negative predictive value of 42.3%, and a predictive accuracy of 88.6%. Parveen et al, 16 Rasheed and Srivastava 17 reported similar findings. These findings support the use of admission CTG in low‐resource settings.…”
Section: Discussionmentioning
confidence: 69%
“…The admission CTG had a high sensitivity of 91.0% in predicting base deficit of >−12 mmol/L, a specificity of 68.8%, a positive predictive value of 96.6%, a negative predictive value of 42.3%, and a predictive accuracy of 88.6%. Parveen et al, 16 Rasheed and Srivastava 17 reported similar findings. These findings support the use of admission CTG in low‐resource settings.…”
Section: Discussionmentioning
confidence: 69%